Rapid reference review in orthopedic trauma : pivotal papers revealed - Hak, David J. (SLACK Incorporated, 2013)
"Are you spending valuable time searching through hundreds of article citations in search of information on a particular injury or treatment? Look to Rapid Reference Review in Orthopedic Trauma: Pivotal Papers Revealed for a quick and succinct way to find the key information and quick facts you need to know instantly. Medical literature continues to expand at an exponential pace and finding the most important information is becoming increasingly difficult. Rapid Reference Review in Orthopedic Trauma: Pivotal Papers Revealed by Dr. David J. Hak offers a simple way to access and review the key points from the most relevant and important published articles. Key references include: - Classic articles - Landmark articles - Up-to-date reviews - Important clinical trials. Each article is formatted to include an article citation, a summation of the abstract, a summary of key points, and author commentary. This enables readers to quickly review key facts from the most important articles and clinical trials in order to effectively plan and guide treatment. Rapid Reference Review in Orthopedic Trauma: Pivotal Papers Revealed is a great literary reference that will prove highly useful to orthopedic residents, fellows, and medical students, as well as practicing and academic orthopedic surgeons."--Provided by publisher.